Mesenchymal stem cell-derived exosomes promote hepatic regeneration in drug-induced liver injury models - Tan, Cheau Yih (Stem Cell Res Ther, 2014)
INTRODUCTION: Mesenchymal stem cell-conditioned medium (MSC-CM) has been shown to have protective effects against various cellular-injury models. This mechanism of protection, however, has yet to be elucidated. Recently, exosomes were identified as the active component in MSC-CM. The aim of this study is to investigate the effect of MSC-derived exosomes in an established carbon tetrachloride (CCl(4))-induced liver injury mouse model. This potential effect is then validated by using in vitro xenobiotic-induced liver-injury assays: (1) acetaminophen (APAP)- and (2) hydrogen peroxide (H(2)O(2))-induced liver injury. METHODS: The exosomes were introduced concurrent with CCl(4) into a mouse model through different routes of administration. Biochemical analysis was performed based on the blood and liver tissues. Subsequently the exosomes were treated in APAP and H(2)O(2)-toxicants with in vitro models. Cell viability was measured, and biomarkers indicative of regenerative and oxidative biochemical responses were determined to probe the mechanism of any hepatoprotective activity observed. RESULTS: In contrast to mice treated with phosphate-buffered saline, CCl(4) injury in mice was attenuated by concurrent-treatment exosomes, and characterized by an increase in hepatocyte proliferation, as demonstrated with proliferating cell nuclear antigen (PCNA) elevation. Significantly higher cell viability was demonstrated in the exosomes-treated group compared with the non-exosome-treated group in both injury models. The higher survival rate was associated with upregulation of the priming-phase genes during liver regeneration, which subsequently led to higher expression of proliferation proteins (PCNA and cyclin D1) in the exosomes-treated group. Exosomes also inhibited the APAP- and H(2)O(2)-induced hepatocytes apoptosis through upregulation of Bcl-(xL) protein expression. However, exosomes do not mitigate hepatocyte injury via modulation of oxidative stress. CONCLUSIONS: In summary, these results suggest that MSC-derived exosomes can elicit hepatoprotective effects against toxicants-induced injury, mainly through activation of proliferative and regenerative responses.